Study of the compressive strength of manganese ore waste briquettes with bentonite - Piassa Varanis, Amanda; Peres Ribas, Ericksen; Gustavo Mendes de Jesus, Leandro (International Journal of Scientific World, 2025)
The primary raw material for ferroalloy production is manganese ore, which is extracted and charged in beneficiation processes that include granulometric adjustment. In the submerged arc furnace, the charging of fine manganese ore particles must be avoided, as an excessive amount can obstruct interstices and consequently channeling within the charge. The briquetting process is a potential solution, as it consists of an agglomeration process for fine particles through the application of pressure. This study aims to evaluate the compressive strength of manganese ore briquettes with bentonite as a binder, considering a set of conditions to maximize briquette compressive strength. The general objective of this study is to analyze compressive strength about curing time, temperature, binder percentage, raw material particle size, and water/binder rate. The results obtained indicate that the best-performing test specimen was the one cured for 28 days, treated at 400°C, with 7,5 % binder, a particle size of 2,00 mm, and a water/binder ratio of 1,25:1.